Semantic Structure of Verb “prisnat’sya” (to confess): Linguoaxiological Aspect - Sergey G. Pavlov; Natalia E. Petrova (Научный диалог)
The article is devoted to the semantic structure of the verb “prisnat’sya” (to confess). The work was carried out in line with the integral description of vocabulary and linguoaxiology. Particular attention is paid to the axiological component of the semantics of the investigated verb. The lexicographic portrayal of the lexeme is applied according to the principles of integral description. It is shown that the verb “prisnat’sya” (to confess) can serve as a metalanguage means of revealing the value components of linguistic units and the realities indicated by them. The material of the study was Russian texts, primarily from the National Corps of the Russian Language, and contexts constructed by the author that are linguistically relevant for solving the problems posed in the article. Interpretations of the verb “prisnat’sya” (to confess) in authoritative dictionaries of the Russian language of the 20th - 21st centuries are critically examined, and its semantic specificity is defined. An explanation of the verb “prisnat’sya” (to confess) in a clichéd expression “prisnat’sya v lyubvi” (to confess one’s love to someone) is offered. The semantic-pragmatic, morphological, syntactic, communicative-prosodic difference between the three groups of uses of the analyzed verb is demonstrated. The first two groups of uses are covered by an axiologically labeled token confess1 , against which the concept of an axiological homonym “prisnat’sya” (to confess)2 is introduced. As a result of the analysis, our own analytical interpretations are proposed “prisnat’sya” (to confess)1 and “prisnat’sya” (to confess)2 . It is concluded that the presuppositional component of its semantics is a semantic factor that ensures the ability of a token “prisnat’sya” (to confess)1 to be a metalinguistic indicator of values.